PENINGKATAN PEMAHAMAN SIKLUS HIDUP PRODUK DAN PEMASARAN DIGITAL PADA KELOMPOK TANI IKAN DI DESA DONOHARJO - Antonius Satria Hadi; Ardhi Khairi; Cahya Purnama Asri; Bhenu Artha; Utami Tunjung Sari (Universitas Sanata Dharma, 2021)
This community service activity to give counseling to fish farmer groups in Dukuh Brengosan, Donoharjo Village, Ngaglik, Sleman, Yogyakarta Special Region which aims to provide additional understanding and knowledge to the fish farmer group